Correction to: Aryl hydrocarbon receptor signaling promotes ORMDL3-dependent generation of sphingosine-1-phosphate by inhibiting sphingosine-1-phosphate lyase. Issue 9 (September 2018) - Wang, Hsueh-Chun; Wong, Tzu-Hsuan; Wang, Li-Ting; Su, Hsiang-Han; Yu, Hsiu-Yueh; Wu, Ai-Hsuan; Lin, Yu-Chun; Chen, Hua-Ling; Suen, Jau-Ling; Hsu, Shih-Hsien; Chen, Li-Chen; Zhou, Yufeng; et al.
In this article, published online 23 March 2018, the affiliation 10 of Zhou Y was incorrect. The affiliation should be "Children's Hospital and Institute of Biomedical Sciences, Fudan University. Key Laboratory of Neonatal Disease, Ministry of Health, 201102, Shanghai, China." The authors regret the errors.